2022
DOI: 10.1007/s10238-022-00848-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and decreased protein expression of ABCG2 urate transporters are associated with susceptibility to gout, disease severity and renal-overload hyperuricemia

Abstract: Gout is a common crystal induced disease of high personal and social burden, characterised by severe arthritis and comorbidity if untreated. Impaired function of ABCG2 transporter is causative in gout and may be responsible for renal-overload type hyperuricemia. Despite its importance, there is limited information on how clinical parameters correlate with protein expression and that with genetic changes. Urate and clinical parameters of 78 gouty patients and healthy controls were measured among standardised ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Unanimous consensus among the authors to include all articles was reached. Of the 17 included publications, six focused on the genetic component of EOG [49][50][51][52][53][54], ten focused on the clinical aspects of EOG [55][56][57][58][59][60][61][62][63][64], and one had aspects of both [65]. Of the clinically focused publications, six were retrospective, cross-sectional comparisons between EOG and CG cohorts [57][58][59][60][61][62], three were prospective comparisons between EOG 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Unanimous consensus among the authors to include all articles was reached. Of the 17 included publications, six focused on the genetic component of EOG [49][50][51][52][53][54], ten focused on the clinical aspects of EOG [55][56][57][58][59][60][61][62][63][64], and one had aspects of both [65]. Of the clinically focused publications, six were retrospective, cross-sectional comparisons between EOG and CG cohorts [57][58][59][60][61][62], three were prospective comparisons between EOG 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…Our systematic literature review identified six full-length publications and one abstract with novel and relevant information related to EOG genetics. Patient and/or gout characteristics were briefly described in the presence of uratetransporter (ABCG2) [49][50][51][52][53], solute carrier (SLC) [53,54], or aldehyde dehydrogenase (ALDH) [53] mutations. Though these mutations are rare in the general population, nearly one-third of a small EOG cohort (7 of 26 patients [27%]) had a ''probably pathogenic'' ABCG2, SLC, or ALDH mutation [53].…”
Section: Genetics Of Early-onset Goutmentioning
confidence: 99%
“…In order to explore the genetic and regulatory background of GLUT1 expression, potentially related to various diseases, first we have studied the expression level of this protein in the human red blood cell membrane. As described earlier, a quantitative estimation of the erythrocyte membrane proteins can be achieved by using our antibody-based flow cytometry technology, which allows for exploring the genetic background of the alterations in membrane protein expression and the connected disease conditions [ 19 , 20 , 21 ]. We have documented that by using this erythrocyte ghost-forming method and applying well-established, specific monoclonal antibodies—in contrast to other technologies (e.g., Western blotting or direct chemical labeling)—even small differences in the red cell expression levels can be properly quantitated.…”
Section: Introductionmentioning
confidence: 99%